Examining the impact of green marketing practices on business performance: A synergistic application of resource-based view and triple bottom line theory - Md. Asaduzzaman Babu; Md. Abdur Rouf; Md. Rohibul Islam; Mahmudul Islam (PLoS ONE, 2026)
The primary focus of this investigation is to assess the influence of green marketing practices and their potential effects on organizations’ operational performance. The factors influencing business performance include environmental, economic, and social elements. Data collection involved 303 respondents who completed a questionnaire utilizing a 5-point Likert scale for each statement. The participants in the study included employees from manufacturing, non-manufacturing, and service sectors. This investigation used a structured equation model (SEM) methodology to assess the impact through the synergic application of RBV and TBL theory, with data analyzed using Smart PLS version 4.1.0.8. The study’s findings indicate that implementing green marketing practices has a positive and significant influence on business performance. Additionally, perceived competitive advantage and green innovation marketing strategy are positive mediators in the relationship between green marketing practices and business performance. The findings indicate that business performance substantially impacts environmental, economic, and social performance. The study’s uniqueness lies in examining perceived competitive advantage and green innovation marketing strategy as a mediating variable. Businesses are increasingly concentrating on the effects of environmentally friendly marketing strategies on their performance; therefore, this study examines how these practices contribute to enhancing business performance. Future investigations may occur in sectors like FMCG, RMG, leather, and others.